Influencer [ the power to change anything - Patterson, Kerry , 1946- (McGraw-Hill, 2008)
"Everyone wants to be an influencer. We all want to learn how to help ourselves and others change behavior. And yet, in spite of the fact that we routinely attempt to do everything from lose weight to improve quality at work, few of us have more than one or two ideas about how to exert influence. For the first time, Influencer brings together the breakthrough strategies of contemporary influence masters. By drawing from the skills of hundreds of successful influencers and combining them with five decades of the best social science research, Influencer shares eight powerful principles for changing behaviors -- principles almost anyone can apply to change almost anything." ... From publisher's description